Testing Of Variation Tray’s Hole Diameter Of Cassava Dryer Cabinet Type To Quality Drying Results - Geri Frandianto Lumbantobing; Ainun Rohanah; Sulastri Panggabean (Universitas Sumatera Utara, 2016)
The dependence of people consume rice is not followed by the increase of rice production. Therefore on, alternative foodstuffs is needed such as cassava which can be processed into gaplek, and cassava flour. This research was done in Agriculture Engineering Laboratory Faculty of Agriculture, and Food Science and Technology Laboratory Faculty of Agriculture in Oktober 2014 until March 2015 using non factorial completely design with tray holes diameter of (D1) 3 mm, (D2) 5 mm, and (D3) 7 mm. The parameters analysed were processing capacity, moisture content, yield, and brightness level. The results, showed that, the best drying cassava is produced by (D2) 5 mm. Keywords : Cassava, Dryer, Tray holes